Single Versus Multi-Faceted Implementation Strategies – Is There a Simple Answer to a Complex Question? A Response to Recent Commentaries and a Call to Action for Implementation Practitioners and Researchers - Gill Harvey; Alison Kitson (International Journal of Health Policy and Management, 2016)
We are increasingly aware of the need to be as effective and efficient as possible when designing and applying strategies to implement evidenceinformed changes into policy and practice, particularly within our resource constrained health systems. Implementation efforts consume a range of resources, including time, people, educational input, and communication systems to name just a few